Organic Zinc as Feed Additive for Ruminants - Suprijati . (Indonesian Center for Animal Research and Development, 2013)
Zinc is an essential micro mineral required by ruminants and is a component of over 300 enzymes which play important role in the metabolisms of carbohydrates, proteins and fats. Recently, the chemical and biotechnology processes have been developed for synthesizing organic Zn. Organic Zn is the product of a chelating process of dissolved Zn anorganic salts with amino acids or hydrolyzed protein. The utilization of organic Zn as feed additive in ruminants diets tends to increase, due to the absorption of Zn in the organic form is more effective than the inorganic form. This paper reviewes the research from comparative studies of inorganic and organic Zn on the growth, production and reproduction in ruminants. The studies found that the supplementation of organic Zn improved nutrient digestibility, growth, feed efficiency, milk production, Zn retention and absorption, production and reproductive performances of ruminants. However, a little variation response was found due to different degrees of chelating on Zn incorporation of amino acids or hydrolyzed protein. Key words: Organic Zn, characteristic, supplementation, performance, ruminants